Justification of structural and technological parameters of microwave installations for heat treatment of wax raw materials. Issue 1 (November 2020) - Novikova, G; Mikhailova, O; Prosviryakova, M; Zaitsev, P; Shevelev, A; Dulepov, D
Abstract: The article is devoted to the development of a method and technical devices that allow separating honey when melting beeswax under the action of an ultra-high frequency electromagnetic field. Analyzed electrical properties of beeswax and honey; the dynamics of heating of components of raw materials; three models of installations with different resonators; investigated the electrodynamic parameters of the system; substantiated the structural-technological parameters of the installation. Three variants of installations for wax melting with different resonators have been developed. In the first installation, the modules contain cylindrical and spherical resonators. In the second installation, a spherical resonator inside a toroidal resonator is installed. In the third installation, two cylindrical resonators in series are connected. In the second installation, the wax raw material is dosed with rolls onto a perforated disk inside a spherical resonator, where the raw material is heated to 40 °C, increasing its fluidity, which allows the honey to be separated when the disk rotates. Effective modes of heating beeswax are: specific power of the generator 0.85 W/g; duration of exposure to ultrahigh frequency electromagnetic field 240 sec; heating temperature of the wax 64 °C.